The influence of vocabulary mastery and reading comprehension of argumentation writing skills - Royan Nur Fahmi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This study aims to determine the effect of variable vocabulary and reading comprehension skills of argument essay writing. Method used is the method of survey with a sample of students of 40 students were taken by random sampling technique from Tunas High School Jaka Sampurna in Bekasi. Data collection using the validated test instrument. Regression equation Y ̂=1,079+0,385X_1 wich means that if the students vocabulary mastery is ignoed, then the ability to write arguments for 1,079. Every adding one point to the vocabulary it will add the ability to write the argument of 0,385 point. Regression equation Y ̂=1,079+0,355X_2 whic means that if reading comprehension is ignored, then the argument of 1,079 skill writing, meaning the reading comprehension is ignored then the ability to write arguments. For each additional 1,079 points in reading comprehension, reading comprehension will add 0,353 points. It can be concluden that the vocabulary and reading comprehension together affect 23,4% of the writing skills of argumentation percent of the value. (koef determinate R2 = 0,234 with the value of the test F = 5,665.